THU0026 A single nucleotide polymorphism on the il-10 locus defines an expression polymorphism and a possible risk factor to develop ra. (1st June 2001) - Lard, LR; Schonkeren, JJ; Pieterman, E; Westendorp, R; Breedveld, FC; Huizinga, TW
Abstract : Background: IL-10 production differs between individuals. We have evaluated the IL-10 production in whole blood cultures with/without LPS. The comparison of monozygotic twins, sibs and unrelated individuals yielded an estimate of heritability of 70%. The IL-10 production was associated with haplotypes defined by alleles of CA-repeats. In line with these results we have demonstrated that the interindividual differences in production of mRNA encoding IL-10 are similar than the interindividual differences in IL-10 protein production. Objectives: To define SNPs associated with common haplotypes, to study the association of IL-10 production with haplotypes/SNPs and to measure the distribution of IL-10 SNPs in RA versus controls. Methods: DNA of high and low IL10 producers were sequenced. Subsequently, the association between LPS-induced IL-10 production and previously described panel was analysed. Results: The following SNPs were identified: -3575 A to G, -2849 A to G, -2763 A to C and -1330 A to G. Previously we have identified 4 ancestral IL-10 haplotypes. The current SNP?s on: IL10.1 R3-AAAA-(IL10G)-GCC, IL10.2 R2-TGCG-(IL10G)-ACC, IL10.3 R2-AGAA-(IL10G)-GCC, and IL10.4 R2-TGCC-(IL10G)-ATA. To investigate whether these SNP?s were functional we analysed the LPS-induced IL-10 production of 161 healthy donors with a specific genotype: -3575: AA (n = 38) 1896 ng/ml, AT (n = 76) 3232 ng/ml, TT (n = 47) 3195 ng/ml. -2849: AA (n = 21) 2115 ng/ml, AG (n = 75) 2950 ng/ml, GG (n = 65) 3111 ng/ml (MW-test both p < 0.05). Next, the analysis was repeated in a different group of donors: 135 partners of patients with SLE/MS: -3575: AA (n = 29) 4190 ng/ml, AT (n = 71) 4521 ng/ml, TT (n = 35) 4401 ng/ml (MW-test P = 0.6). -2849: AA (n = 26) 3845 ng/ml, AG (n = 41) 4577 ng/ml, GG (n = 68) 4543 ng/ml (MW?test P = 0.04, for G carrier versus non G: P = 0.02). Next, the distribution of -2849 SNP was compared in RA patients compared to controls. Control-Panels were 1) partners of MS-SLE patients and 2) organ donors. RA-patients were: 1) incident RA cases, 2) outpatient consecutive RA and 3) RA patients from our early arthritis cohort. Control 1) AA 27, AG 42, GG 71; 2) AA 16, AG 64, GG 88; RA patients 1) AA 3, AG 38, GG 51; 2) AA 24, AG 141, GG 152; 3) AA 16, AG 74, GG 91. Total chi-square: P = 0.0014. Conclusion: We have previously found that the allele IL-10R3 microsatellite was less frequent in three ethnic groups of RA patients (Afro-americans p < 0.01, English p < 0.008 and Scottish p < 0.02). The SNP that defines the haplotype on which R3 is located is also less prevalent in three groups of dutch RA compared to two groups of dutch controls. These data suggest that a high innate IL-10 production is a risk factor for RA. This may be due to the B-cell stimulating properties of IL-10.